Pharmacokinetics of diminazene in plasma and lymph of goats - Mamman, M.; McKeever, Declan J.; Aliu, Y.O.; Peregrine, A.S. (1996)
Diminazene aceturate is one of a limited number of drugs currently being used in animals to treat the tsetse fly-transmitted protozoal disease, African trypanosomiasis. Efficacy of the drug at the recommended single IM administered doses of 3.5 and 7.0 mg/kg of body weight is widely acknowledged. However, resistance to the drug at these dosages has been reported. Although the mechanisms of resistance to diminazene are poorly understood, field and experimental data indicate that it may develop naturally through administration of subcurative doses, or as a result of cross-resistance. Evidence from other experimental studies indicates that there are additional mechanisms by which trypanosomes may develop resistance to diminazene aceturate. For instance, some populations ot Trypanosoma brucei and T. vivax are refractory to treatment because of their ability to invade the CNS, a site that is believed to be poorly accessible to diminazene. Furthermore, in recent studies carried out in goats, it has been documented that the ability of T. Congolense IL 3274 to survive treatment with diminazene depends on the stage of infection when treatment is administered; populations of the parasite reappeared in animals that were treated on day 19 after tsetse fly challenge, whereas all goats were cured when treated on day 1 of infection. Because trypanosomes are confined to the skin on day 1 after infection, but thereafter invade the blood circulation, it is possible that the efficacy of the treatment on day 1 is attributable to exposure of the small number of parasites, relative to later stages of infection, to higher concentrations of drug than those attained in blood. The objective of the study reported here was to determine whether diminazene's pharmacokinetics differ between plasma and lymph draining the skin of goats and therefore account for the variation in therapeutic activity of the drug at different stages of a tsetse fly-transmitted infection. Peripheral lymph was used for this work because it appears to be identical in composition to tissue interstitial fluid, into which trypanosomes are inoculated by infected tsetse flies when feeding.